BUILT ENVIRONMENTAL FACTORS AFFECTING URBAN PROPERTY CRIMES IN SRI LANKA - De Silva, Banuka; Buddhadasa, Anuruddhika; Ranaweera, K.G.N.U. (Universitas Hasanuddin, 2023)
The study has revealed significant associations between built factors and property crimes. Factors such as strong locks, security gates, security cameras, lighting conditions, visibility, and access points are identified as key determinants of property crime rates. The results suggest that improving lock security measures, installing security gates and cameras, enhancing lighting conditions, and increasing visibility can effectively reduce the incidence of property crimes. The findings contribute to the existing body of knowledge on crime prevention and urban planning, providing valuable insights for policymakers, urban planners, and law enforcement agencies. The study recommends the implementation of targeted interventions and strategies to mitigate property crimes and create safer urban environments in Sri Lanka. Further research is encouraged to explore additional factors and develop comprehensive frameworks for crime prevention in urban settings.